2022
DOI: 10.12775/jehs.2023.13.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Motivations in weight reduction and undesirable eating behaviors among women with excessive body weight (Poland)

Abstract: The aim of this study was to evaluate the relationship between attitudes toward weight loss, taking into account: the motivating factors that determine the desire to attempt weight loss; the level of well-being and degree of motivation before and during the weight loss attempt; changes in attitudes after an unsuccessful weight loss attempt; the state of well-being after the completed weight loss attempt and the degree of severity of disordered eating according to the TFEQ-13 questionnaire. The study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another study, which involved 529 adult participants and 358 adolescents, discovered that girls exhibiting higher scores in restrained eating consumed fewer calories than their counterparts, while those characterized as emotional eaters had a greater intake of snack foods ( 80 ). According to results, emotional eating and uncontrolled eating are positively correlated in both genders, with the relationship being stronger in females ( 79 , 81 ). The literature further emphasizes that orthorexia itself may be a response to negative emotions experienced by creating a way of coping ( 82–85 ).…”
Section: Discussionmentioning
confidence: 95%
“…Another study, which involved 529 adult participants and 358 adolescents, discovered that girls exhibiting higher scores in restrained eating consumed fewer calories than their counterparts, while those characterized as emotional eaters had a greater intake of snack foods ( 80 ). According to results, emotional eating and uncontrolled eating are positively correlated in both genders, with the relationship being stronger in females ( 79 , 81 ). The literature further emphasizes that orthorexia itself may be a response to negative emotions experienced by creating a way of coping ( 82–85 ).…”
Section: Discussionmentioning
confidence: 95%
“…Lee and Hong [27] reported that women who considered themselves obese were more likely to try to lose weight. The possible reasons for participation in weight loss are that people are already diagnosed with cardiovascular disease and are trying to improve their health status [53]. Sirirassamee et al [54], on the other hand, argued that women who mistakenly believe that they are overweight may not try to lose weight.…”
Section: Discussionmentioning
confidence: 99%